Gender-Segmented Labor Markets and Trade Shocks - Carlos Goes; Gladys Lopez-Acevedo; Raymond Robertson (Institute of Labor Economics (IZA), 2023)
This paper focuses on how gender segmentation in labor markets shapes the local effects of international trade. We first develop a theoretical framework that embeds trade and gender-segmented labor markets to show that foreign demand shocks may either increase or decrease the female-to-male employment ratio. The key theoretical result shows formally that the effects of trade on gender-segmented labor markets depend crucially on (a) the sectors that face the foreign demand shock; and (b) the domestic relevance of the foreign countries in which the demand shocks originate from. If the foreign demand shock from a relevant market happens in a female-intensive (male-intensive) sector, the model predicts that the female-to-male employment ratio should increase (decrease). We then use plausibly exogenous variation in the exposure of Tunisian local labor markets to foreign demand shocks and show that the empirical results are consistent with the theoretical prediction. In Tunisia, a country with a high degree of gender segmentation in labor markets, foreign-demand shocks have been relatively larger in male-intensive sectors. This induced a decrease in the female-to-male employment ratio, with households likely substituting female for male labor supply.
Keywords: F16; J16; O19; 330; international trade; labor markets; gender; inequality